Gender issue in contract farming: the case of Malaysian students - Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva; Uli, Jegak; Abu Samah, Bahaman (Science Publications, 2010)
Problem statement: Agriculture has been proved to be a significant impetus for development in Malaysia. Agriculture offers a number of profitable activities, contract farming is one of it and it is still in infancy stage. Besides being a developed sector in Malaysia, it still has a number of problems to be solved. Gender issue is one of it. Gender issue in agriculture has become more crucial these days. To sustain the agriculture sector especially contract farming, an equal level of acceptance, attitude and knowledge towards contract farming should be gained between male and female. Approach: This study investigated whether male and female have any difference on acceptance, attitude and knowledge towards contract farming. Data was gained through a survey questionnaire on 400 male and female youth who are currently studying in various tertiary institutions throughout Malaysia. For the purpose of analyses, PASW software was used where descriptive and inferential analyses were employed. Results: Male and female youth were found to have a good and positive level on acceptance, attitude and knowledge towards contract farming. Based on the independent t-test done, male and female youth possessed equal level of acceptance, attitude and knowledge towards contract farming. Conclusion/Recommendations: Results gained bring us to the conclusion that contract farming has a huge potential to attract youth to be part of agriculture community. To transform this potential agricultural method to a reality, more promotion, exposure and information on contract farming should be given to the youth. It was recommended that related agriculture agencies, Department of Women Development and agriculture related universities to take the responsibilities of exposing contract farming activities to the youth in Malaysia.